DISSEMINAÇÃO DO CONHECIMENTO TÁCITO NA GESTÃO DO CONHECIMENTO: ESTUDO DE CASO EM UM ESCRITÓRIO DE ADVOCACIA - Silva, Kristie Vasconcelos da (2010)
The objective of this paper was to do a scientific investigation in one of the major Law Firms in Brazil, according to the specialized guide Latin Lawyer, aspects about Knowledge Management (KM). Hence identifying in the target of such study the propagation and conversion process of the tacit knowledge to tacit (socialization), and tacit to explicit (externalization), in accordance with the model of a dialectic enterprise that has been considered innovative in the Eastern World, also checking if this model has been implemented, and pointing out the possible difficulties for the dissemination of the knowledge in the respective stages. In order to reach such objectives an exploratory survey was performed by means of a case study. The study was based on the analysis of multiple evidences: closed-ended questionnaire, semistructured interviews, analysis of documents, and direct observation. The results were arranged by the software SPSS (Statistical Package for the Social Sciences), and in order to check the reliability of the instrument the Cronbach Alpha was checked and the result was 0,94. It was possible to conclude from this study that although the Law firm had not formally implemented the model of the dialectic enterprise of the Japanese theorists Nonaka and Takeuchi, it meets all of the necessary preparatory conditions for the creation of organizational knowledge, as well as for the process of conversion and propagation of such knowledge.